Determination of the optimal modes of operation of the clover grater and scarifier KS-0.3 P during scarification - A. I. Burkov; A. L. Gluhkov; V. A. Lazukin; V. Yu. Mokiev (Аграрная наука Евро-Северо-Востока, 2023)
The article provides information about the features of the device, the quality of work of the prototype of a new 25...30 % more productive clover grater and scarifier KS-0.3 P in comparison with the analogue KS-0.2 P. KS-0.3P includes a drum-type wiping and scarifying device, a pneumatic separation device, a two-stage exhaust air purification system containing a cyclone and a fabric filter. The increase in the productivity of the new machine is achieved by increasing the diameter of the drum with a solid wiping surface to 0.45 m and the length of the oval deck with scarifying plates to 0.7 m. The solid grating surface of the drum is welded from steel rods of hexagonal profile No. 12 mounted on an edge. The deck covering the drum from below by 180° is made of round bars with a diameter of 10 mm and nine steel plates with a thickness of 2 mm and a width of 11 mm, evenly distributed along the length of the deck. When studying the technological process of clover grater and scarifier the method of mathematic planning of the experiment was used. The quality of scarification done was evaluated using the GOST 12038-84, GOST 12036-85 methodologies and additionally introduced indicator of variation of the number of germinated seeds. The material supply was regulated by the degree of opening of the flap in the loading hopper in the range from 0.2 to 0.4 t/h. The rotation frequency of the drum was changed by a frequency converter from 550 to 650 min-1. Eastern galega seeds met GOST 52325-2005 requirements. The experiments were carried out in three-fold repetition. As a result of an experimental study of the KS-0.3P cloverworm-scarifier during the scarification of the seeds of the Eastern galega, the ranges of the optimal drum rotation speed of 550... 650 min-1 and the material supply of 0.3... 0.4 t / h were determined, when the specified agrotechnical indicators were provided: the degree of scarification not less than 95.0 % and crushing not more than 1.5 %.